Trapped Charged Particles - A Graduate Textbook with Problems and Solutions - Niels Madsen (Trapped Charged Particles, 2016)
At Les Houches in January 2015, experts in the field of charged particle trapping came together for the Second Winter School on Physics with Trapped Charged Particles. This textbook collates the lectures delivered there, covering the fundamental physics of particle traps and the different types of applications of these devices.Taken as a whole, the book gives an overview of why traps for charged particles are important, how they work, their special features and limitations, and their application in areas such as precision measurements, mass spectrometry, optical clocks, plasma physics, antihydrogen creation, quantum simulation and quantum information processing. Chapters from various world experts include those on the basic properties of Penning traps and RF traps, as well as those covering important practical aspects such as vacuum systems, detection techniques, and different types of particle cooling, including laser cooling.Each individual chapter provides information and guidance on the application of the above methods. Additionally, each chapter is complemented by fully worked problems and solutions, making Trapped Charged Particles perfect for advanced undergraduate and postgraduate students new to this topic.